(untitled) (Journal of Current and Advance Medical Research, 2019)
Background: Several drugs are used individually for migraine prophylaxis. Objective: The purpose of the present study was to compare the propranolol and amitriptyline as monotherapy for the prophylaxis of migraine. Methodology: This randomized control trial was conducted in headache clinic at Banghabandhu Sheikh Medical University (BSMMU), Dhaka, Bangladesh from July 2012 to June 2014 for a period of two (02) years. Migraine patients with or without aura of 16 to 50 years of age, patients not on any prophylactic medication were included for this study. Patients meeting all the criteria was randomized group A who were treated with Amitriptyline and group B who were treated with propranolol. Patients was followed for a three months period during which they was instructed to maintain a headache diary. The primary outcome evaluated was the proportion of patients in each group that achieved a 50% reduction in the number of days with headache. Result: A total 80 adult patients were selected. During 1st visit among the patients duration of pain 1 to 4 hours (2.5.0%), 5 to 8 hours (13.3%) 9 to 12 hours (35.0%) and above 13 hours (22.5%) in group A were recorded; however, in group B, duration of pain 1 to 4 hours 1(2.5), 5-8 hours 16(13.3%), 9-12 hours 19(47.5) and above 13 hours 4(10.0) (p>0.05). In group A, no adverse effect was found 26(65.0%), drowsiness 6 (15.0%), dryness of mouth 6(15.0%), constipation 2(5.0%), fatigue and bradycardia were not found. In group B, no adverse effect was found 29(72.5%), drowsiness, dryness of mouth and constipation were not found, fatigue and bradycardia were 7(17.5%) and 4(10.0%). Conclusion: In conclusion number of attack and headache before treatment gradually decrease in subsequent follow up in both groups. Journal of Current and Advance Medical Research 2019;6(2):77-82